Designing a Dashboard for Sales Trends and Analysis at Coventown Glodok Jakarta - Tasya Mulia Salsabila; Jap Tji Beng; Dedi Trisnawarman; Sri Tiatri; Toong Hai Sam; Ele Lunzaga; Rahmiyana Nurkholiza; Vienchenzia Oeyta Dwitama Dinatha (STMIK Banjarbaru, 2025)
Coventown is a coffee shop with a Chinese theme located in the Petak Enam Glodok area, Jakarta. The sales dashboard design allows Coventown Glodok Jakarta to identify sales patterns, and predict sales performance through historical data analysis. This study aims to present data in easy-to-understand visualizations to demonstrate the use of dashboards in improving the efficiency of sales monitoring, providing strategic insights into trends, and achieving sales targets to support more precise and effective decision-making. The prototype development iterations were planned quickly, and the data was processed using Microsoft Power BI and the Python programming language. The results of this study show that the sales dashboard at Coventown Glodok Jakarta effectively monitors sales in line with Key Performance Indicators (KPIs) such as time, category, product, price, and quantity. The resulting dashboard improves the efficiency of monitoring sales performance and helps the company display sales trends for best-selling products.